Exploring the Impact of Proactive Personality on Sosial Capital through Internet Self-Efficacy and Online Interaction Quality - Yunina Resmi Prananta; Suwito Eko Pramono; Martono Martono (International Conference on Science, Education, and Technology, 2022)
During the COVID-19 crisis, traditional learning has suddenly turned into digital learning, which ultimately poses challenges for students and teachers. During the COVID-19 pandemic, the influence of personality factors on students' social networks appears to be a neglected area of ​​research. In this study, we aimed to explore the relationship between proactive personality and social capital through underlying mechanisms (such as internet self-efficacy and online interaction quality), particularly to obtain data during the peak of the COVID-19 pandemic. In addition, this study also aims to examine the moderating role of perceived social support in the relationship between proactive personality and internet self-efficacy and the relationship between proactive personality and online interaction quality. Similarly, the moderating effect of perceived social support also investigated the mediating effect of Internet self-efficacy & online interaction quality. This study used a survey tool to collect data from 332 respondents, including students and teachers from Wonosobo, an area in Central Java. In this study, we found that students' proactive personalities strengthened their social capital through the quality of online interactions during the COVID-19 pandemic. Similarly, perceived social support amplifies the mediating effect of online interaction quality in the relationship between proactive personality and social capital during the COVID-19 pandemic. Furthermore, the implications and directions of future research are also discussed.